Education in Japan: testing the limits of asian education (Foro de Educacion, 2011)
A re-imagining of education is taking place throughout the world with the 21st century in mind and nowhere is this being tested, probed, and critiqued more than in Asia. This new era sees social phenomena as polycentric and polycontextual rather than bilateral or unidirectional. Asia is first and foremost where education in the 21st century is seeing its most spectacular engagement and growth. We view the Japa- nese example with its multiple, textured approaches as one of the heralds of this new global conversation for an education that responds to the transnational, transcultural characteristics of the new age that has daw- ned upon us. Combining Confucian, North American, European, and global approaches – all of which are having an impact on other nations of Asia – Japan represents the cutting edge of a new wave for understan- ding education that has movement as a central motif and strategy.